Diagnostic Accuracy Of Barium Swallow For Dysphagia, Keeping Rigid Esophagoscopy As The Gold Standard - Akram, Ansa Umara; Chaudhry, Sadia; Masood, Sundas; Kausar, Amna; Naveed, Seema; Manzoor, Areesha (Journal of Rawalpindi Medical College, 2023)
Objective: To determine the diagnostic accuracy of Barium Swallow in detection of patients presenting with dysphagia. Study Design: Cross-sectional validation study. Study Setting & Duration: Department of Otorhinolaryngology, Head & Neck Surgery, District Headquarter Hospital Rawalpindi from 01-09- 2022 to 01-03-2023. Materials and Methods: Approval of the study was obtained from the Hospital Ethical Committee. A total of 111 patients both male and female patients were selected. The patients suffering from dysphagia as per operational definitions and who have reported for work-up to the Department of ENT, District Headquarters Hospital, Rawalpindi, and fulfill the complete inclusion and exclusion criteria, were selected. Informed consent was obtained from all the patients. Patients were selected by consecutive non-probability sampling technique. The data was analyzed using SPSS 24. Results: A total of 111 patients were included in this study. The mean age of these patients was 50.79 ± 13.01 years, ranging from 28 to 70 years. The frequency distribution of females 70.27 % was found to be more than that of males 29.73 %. Majority of patients' barium swallow (74.77%) revealed pathologies, while only a small percentage of patients (25.23%) had normal barium swallow. Most of patients (87.39%) had pathologies found during rigid esophagoscopy, while just a small number (12.61%) had normal rigid esophagoscopy. Comparing both investigating tools, esophagoscopy discovered 87.39% of pathologies while Barium swallow detected 74.77%, indicating that esophagoscopy was a more accurate procedure. Patients had esophageal web 55 (25.2%) on barium swallow and 69 (62.2%) on the Rigid esophagoscopy. Barium Swallow had esophageal stricture 28 (52.2) and no Pathology was detected in 28 (25.2 %) patients. As well as Rigid esophagoscopy had esophageal growth13 (11.7), esophageal stricture 15 (13.5), and no Pathology was detected in 14 (12.6 %). Rigid esophagoscopy is more efficient in detecting esophageal pathology than Barium Swallow. In Barium swallows most patients had esophageal web 55 (25.2%) than the esophageal stricture 28 (52.2) and no pathology was detected 28 (25.2). In rigid esophagoscopy most patients had esophageal web 69 (62.2%) than the esophageal growth13 (11.7), esophageal stricture 15 (13.5) and no pathology detected 14 (12.6). Conclusion: A range of diseases are associated with dysphagia can be found in patients. Two often used diagnostic methods are barium swallow and rigid esophagoscopy. Both Barium swallow and Rigid esophagoscopy are successful in the diagnosis of esophageal cancer. The use of a Rigid esophagoscopy is still a gold standard diagnostic and therapeutic tool for upper aerodigestive tract pathologies.